CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS UNDERGOING MONOPOLAR TRANSURETHRAL RESECTION OF BENIGN PROSTATIC HYPERPLASIA AT HA TINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with benign prostatic adenoma undergoing monopolar transurethral resection of the prostate at Ha Tinh General Hospital.Materials and Methods: A retrospective descriptive study on 60 patients with benign prostatic hyperplasia (BPH) who underwent transurethral resection of the prostate (TURP) from January 2023 to December 2025 at Ha Tinh General Hospital.Results: The mean age was 76.25 ± 7.9 years. The most common presenting complaints were acute urinary retention (48.33%) and dysuria (43.33%). Most patients had severe symptoms (mean IPSS 21.53 ± 4.04) and impaired quality of life (mean QoL score 4.8 ± 0.85). The mean prostate volume was 67.28 ± 27.29 g.Conclusion: Patients with prostatic adenoma were predominantly elderly, presenting with severe lower urinary tract symptoms and markedly impaired quality of life. Prostate size was mainly in the moderate-to-large range, indicating suitability for transurethral resection of the prostate using monopolar electrosurgery.
Keywords: Prostatic adenoma; transurethral resection of the prostate.